Tinjauan Yuridis terhadap Pengangkatan Anak Yatim Piatu dalam Perspektif Hukum Perdata Indonesia - Ni Nengah Eilsa Ayu Mediana (Pemuliaan Keadilan, 2026)
Adoption is an act of adopting a child which, according to legal regulations, transfers the rights and responsibilities of the child from their biological parents to their adoptive parents. This study aims to examine the legal framework governing the legal determination of adopted children. This research was conducted using a juridical-normative research approach. This study focuses on reviewing the status of an adopted child, including their position in obtaining inheritance rights, using a review of the Civil Code and other applicable regulations. Based on the analysis that has been carried out, the position or status of a child adopted by adoptive parents has a legal status if it is carried out through applicable legal procedures, which means that the child has equal rights to biological children. This research is expected to contribute to providing references for firmness in family law that is more certain and does not harm any party.